1999
DOI: 10.1086/520450
|View full text |Cite
|
Sign up to set email alerts
|

Aortitis Due toSalmonella: Report of 10 Cases and Comprehensive Review of the Literature

Abstract: We describe ten cases of aortitis due to Salmonella that were treated at the University of Toronto-affiliated Hospitals between 1978 and 1997. Predisposing conditions included hypertension, diabetes mellitus, and myelodysplastic syndrome. Main presenting symptoms were fever and abdominal and back pain. The most frequent site involved was the abdominal aorta, followed by the thoracic aorta. All but one patient were treated with intravenous bactericidal antibiotics; seven also underwent surgery, four with axillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
230
1
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(243 citation statements)
references
References 64 publications
3
230
1
9
Order By: Relevance
“…A prospective case-control study is urgently called for. According to a review of 140 cases of aortitis due to Salmonella reported in the literature since 1948, the most common site of infection is the abdominal aorta, more precisely its infrarenal portion (131). The most common clinical features consisted of fever, abdominal pain, and/or back pain, the last of which may be related to the site of involvement (131).…”
Section: Clinical Spectrum Of Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A prospective case-control study is urgently called for. According to a review of 140 cases of aortitis due to Salmonella reported in the literature since 1948, the most common site of infection is the abdominal aorta, more precisely its infrarenal portion (131). The most common clinical features consisted of fever, abdominal pain, and/or back pain, the last of which may be related to the site of involvement (131).…”
Section: Clinical Spectrum Of Infectionmentioning
confidence: 99%
“…According to a review of 140 cases of aortitis due to Salmonella reported in the literature since 1948, the most common site of infection is the abdominal aorta, more precisely its infrarenal portion (131). The most common clinical features consisted of fever, abdominal pain, and/or back pain, the last of which may be related to the site of involvement (131). A computed tomographic (CT) scan with contrast enhancement is considered the method of choice to diagnose mycotic aneurysm because of its ability to detect early changes in the arterial wall and the periaortic tissue (63,131).…”
Section: Clinical Spectrum Of Infectionmentioning
confidence: 99%
See 3 more Smart Citations